Análise do gerenciamento de cooperativas de materiais reciclados - Nallis, Bruna Golinelli [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
With the technological advance and the easy access to industrialized products the generation of solid waste caused by the exacerbated consumerism has become a problem to be faced, due to the slow speed with the products decomposes and the self-impact degree that these can cause to the environment. Co-operatives of recycled material are an alternative to reduce the amount of solid waste that is destined for landfills or even dumps, through the recycling of materials. The management of these cooperatives depends on the infrastructure of the place where they are inserted, the support they receive and the amount of material they collect, these issues influence the quality of the work done by the cooperative. The present work consists in a analysis of cooperatives Cooperviva (Rio Claro / SP) and Coopervida (São Carlos / SP) from a study of a direct analysis of the cooperative, with interviews and a questionnaire content basic information for managers and cooperative, with the intuition to diagnose the impacts of cooperatives in the municipalities where they are inserted and to point out solutions for their functional improvement. One of the main gaps found in management within cooperatives is the lack of municipal support, often due to a lack of specific legislation within municipalities that shows interest in cooperatives, as well as the lack of knowledge of the population about what solid waste is, as discarded them and discards them properly. Thus, it is necessary to work together within the municipalities studied so that solid waste management is in accordance with the National Solid Waste Policy (PNRS)

Com o avanço tecnológico e o fácil acesso a produtos industrializados a geração de resíduos sólidos causada pelo consumismo exacerbado tem se tornado um problema a ser enfrentado, devido à baixa velocidade com que os resíduos sólidos se decompõe e o auto grau de impacto que esses podem causar ao meio ambiente. As cooperativas de material reciclado são uma alternativa para diminuir a quantidade de resíduos sólidos que são destinados a aterros ou até mesmo lixões, promovendo assim, a reciclagem dos materiais. O gerenciamento dessas cooperativas depende da infraestrutura do local onde é inserida, do apoio que recebem e da quantidade de material que coletam, esses quesitos influenciam na qualidade do trabalho realizado pelos cooperados. O trabalho apresentado consiste em uma análise das cooperativas Cooperviva (Rio Claro/SP) e Coopervida (São Carlos/SP) a partir de um estudo de análise direta da cooperativa, com entrevistas e um questionário contento informações básicas para os gestores e cooperados, com o intuído de diagnosticar os impactos das cooperativas nos municípios onde estão inseridas e apontar soluções para o melhoramento funcional delas. Uma das principais lacunas encontradas na gestão dentro das cooperativas é a falta de apoio municipal, muitas vezes por carência de uma legislação específica dentro dos municípios que demonstre interesse pelas cooperativas, além da falta de conhecimento da população sobre o que são resíduos sólidos, como descarta-los e onde descarta-los de maneira adequada. Assim, é preciso um trabalho conjunto dentro dos municípios estudados para que o gerenciamento dos resíduos sólidos esteja de acordo com a Política Nacional de Resíduos Sólidos (PNRS)
Keywords: Resíduos; Resíduos sólidos; Cooperativas; Produtos reciclados; Reaproveitamento (Sobras, refugos, etc.); Impacto ambiental; Lixo - Eliminação; Desenvolvimento sustentável; Rio Claro (SP); São Carlos (SP)